Effectiveness of bevacizumab and cetuximab in metastatic colorectal cancer across selected public hospitals in Queensland. Issue 5 (20th July 2016) - Chapman, Suzannah J; McKavanagh, Daniel; Burge, Matthew E; McPherson, Ian; Walpole, Euan; Hollingworth, Samantha A
Abstract: Aim: Metastatic colorectal cancer has a large burden of disease in Australia. Medical therapy is fundamental to extending survival and improving quality of life. The benefits of two costly medicines, bevacizumab and cetuximab, used in Australia remain unclear. The aim of this study was to retrospectively examine the use of these two medicines in metastatic colorectal cancer across five public hospitals in south east Queensland and to compare clinical outcomes to those of published clinical trials. Methods: We extracted data from the chemotherapy prescribing database for patients planned for bevacizumab or cetuximab therapy between 2009 and 2013. Median overall survival was estimated using Kaplan–Meier methods. Results: There were 490 bevacizumab‐containing protocols planned and 292 patients received at least one dose of bevacizumab. Median overall survival was 17.2 months (95% confidence interval [CI], 15.4–19.3). Of 208 planned cetuximab‐containing protocols, 134 patients received at least one dose of cetuximab. Median overall survival was 9.1 months (95% CI, 7.6–12.0). Thirty‐day mortality rates from date of first dose were 0.7% for bevacizumab and 7.5% for cetuximab. Conclusion: Overall survival of patients receiving bevacizumab and cetuximab was consistent with clinical trials, providing some assurance that benefits seen in trials are observed in usual practice. This study provides a methodology of using routinely collected health data for clinical monitoring and research. Because of the high cost of these medicines and the lack of toxicity data in this study, further analysis in the postmarketing setting should be explored.